POLA MESTRUASI DENGAN ANEMIA PADA REMAJA PUTRI DI KLINIK AULIA HUSADA, JETIS, MOJOKETO - Sri Wardini Puji Lestari; Zulfa Rufaida; Ika Yuni Susanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2018)
Teen anemia caused by lack of iron intake also occurs due to increased iron requirement in the body such as menstruation. The abnormal pattern of mestruation causes too much blood to come out. This study aims to determine the relationship of menstrual pattern with anemia in young women.. Research design used was a correlational research. Using cross-sectional design. Variable independent menstrual patterns in adolescent girls and the dependent variable anemia in adolescent girls. Sampling technique used was simple random sampling with a population sample of 115 respondents and the amount of 73 respondents. Data were collected during April 1-31 May 2018 the instruments used interviews, checklist and Hb observation. Analysis Technique with square test. The results of research from 73 respondents known 45 respondents (61.7%) experienced abnormal menstrual pattern, 41 (56.2%) had anemia. The result of chi square test shows that ρ = 0,002 <ρ ​​= 0,05 and X2count = 9,409 bigger than X2table. = 7,984. 95% CI does not pass the number 1 is 0.03 - 0.06. Thus, it can be concluded that H0 rejected and H1 accepted means there is a relationship of menstrual pattern with anemia in adolescent daughter. And teenage daughter who experience menstrual pattern disorder risk 3-6 times have anemia. As it is known that menstrual irregularity causes too much blood to come out can cause anemia. So Teenagers can make prevention efforts to keep the nutritional intake of adolescents every day and drink tablet fe at the time of menstruation.